Twisted flicks - Zafra, Jessica (Pasig City Anvil Publishing, Inc., 2003)
A collection of Zafra's film reviews. Her critiques have the kind of bite that engages the readers with the sneer and snarl of an avid movie fan. Her readers and subjects, young and old, will be outraged and amused at her vicious takes on award-winning, top-grossing films.
Keywords: Philippine essays (English)